2012
DOI: 10.5455/medarh.2012.66.s11-s15
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Epidemiological Features of Acute Corrosive Poisonings

Abstract: B ackground: the ingestion of chemical agents, of caustic nature, represents a serious problem for clinical toxicology. If the ingestion doesn't cause death during the acute period, it will most often cause severe side effects in the upper gastrointestinal tract during the chronic phase. Aims: The purpose of this study is to show the clinical, epidemiological and socio-economical characteristics seen in acute corrosive poisonings such as ingested caustic agents, causes for abuse and most consequential complica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
18
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 19 publications
4
18
0
Order By: Relevance
“…This study found that most of cases ingested alkaline caustic agents (48.9%). Many studies reported that alkaline agents are the most common and widely spread caustic agents used as household and industrial cleaners and are easily available at home (Lakshmi et al,2013).While, Chibishev et al (2012) found that, toxicity was commonly due to acidic agents compared with alkaline agents.…”
Section: Discussionmentioning
confidence: 99%
“…This study found that most of cases ingested alkaline caustic agents (48.9%). Many studies reported that alkaline agents are the most common and widely spread caustic agents used as household and industrial cleaners and are easily available at home (Lakshmi et al,2013).While, Chibishev et al (2012) found that, toxicity was commonly due to acidic agents compared with alkaline agents.…”
Section: Discussionmentioning
confidence: 99%
“…The present study showed that alveolar opacities were seen in chest X-ray in 75% of corrosive poisoning cases due to aspiration pneumonitis. Chibishev et al, (2012) reported that patients poisoned by any corrosive substance can develop respiratory complications which depend on the type and the concentration of the corrosive substance.…”
Section: Discussionmentioning
confidence: 99%
“…The time elapsed from acid ingestion to hospitalisation varied between one and six hours [(3.45±1.36) h], that is, well within the optimal time frame for urgent EGD of less than 24 h after ingestion (9).…”
Section: Resultsmentioning
confidence: 99%